Empirical Decomposition and Forecast of Carbon Neutrality for High-End Equipment Manufacturing Industries - Lu, Hang; Elahi, Ehsan; Sun, Zhenya (Frontiers in Environmental Science, 2022)
The Chinese government focuses on the high-end equipment manufacturing industry to achieve a target of carbon neutrality. This study takes China’s Bohai Rim as a case study. First, the Tapio decoupling model was used to analyze the carbon emission status of the high-end equipment manufacturing industry in the Bohai Rim. Second, LMDI was used to determine the main factors of carbon emission. Similarly, the Monte Carlo simulation predicted the time of carbon neutrality. The results found that the relationship between carbon emission and the development of the high-end equipment manufacturing industry is that of strong decoupling, but there is still a risk of “recoupling.” The scale effect is the primary driving force for carbon emission reduction in the equipment manufacturing industry, followed by a structural effect and a carbon emission intensity effect. In the baseline scenario, low-carbon scenario, and technological breakthrough scenario, carbon neutrality will be achieved before 2060. The results of the study suggest that China should improve energy utilization efficiency and encourage green innovation.